STUDY OF SOME RISK FACTORS SUCH AS THE CAUSE OF MUSCLE IMBALANCE AND LUMBAR PAIN - P. Angelova (Trakia Journal of Sciences)
Back pain is a significant public health problem – 11-12% of the population suffers from back pain. The aim of the study is to establish the etiology of lumbar pain, the presence of muscle imbalance and a feeling of pain. Materials and methods: the research is conducted of 2018/2019 at the rehabilitation center Kinezi, Stara Zagora, Bulgaria; health outcome data were collected by Test for muscle stiffness, VAS and Roland-Morris Questionnaire. The mean age of all participants (n = 37) is 44.3 ± 15.3 (17-70) years. Results: the mean (±SD) score of VAS of all studied patients at baseline was 5.78±2.23; the mean (±SD) RMQ score at baseline was 6.95±4.57. The percentage of those who are never and currently not practicing sport is predominant, and the athletes are just under 1/4. The studied as a risk factor causes of muscle imbalance are divided into 4 groups: trauma; physical exertion; static load-sitting or standing for a longer time or as a working posture; spinal deformities. Conclusion: no statistical significance is observed between the cause and the hypertonus of the examined muscles. In women, it is the most pronounced cause of muscle imbalance there at static load (61.9%), and for men at physical exertion (42.8%).